REPOSITIONING AS AN INTERVENTION FOR STROKE PATIENTS WITH PRESSURE ULCER RISK - A CASE STUDY - Pratiwi, Rizky Meuthia; Endah, Umi (Departement Research and Community Engagement Bina Sehat PPNI Institute of Health Science, Indonesia, 2025)
he risk of pressure ulcers are a risk that can occur in patients with stroke. Limited activity and disorders of motor nerves make it difficult for patients to mobilize, resulting in prolonged bed rest. If the risk of pressure sores is left unchecked, a new problem will emerge, namely pressure sores or what is known as pressure ulcers. Repositioning is one solution so that patients can mobilize even in bed. The aim of this research was to conduct a case study analysis of two stroke patients who experienced immobilization and were at risk of pressure ulcers. Using descriptive design with interview techniques, observation, physical examination and documentation. The Braden score instrument is also used as a basis for assessing the risk of decubitus pressure ulcers before and after repositioning. The results of the initial assessment showed that client 1 had a Braden scale score of 10, client 2 had a Braden score of 13 and client 3 had a Braden score of 14, meaning a high risk of pressure sores. Next, repositioning intervention was carried out for 3 days every 2 hours. Other implementations include monitoring weight and changes, using barriers such as lotion or water-absorbing pads at pressure points or bony prominences, patients are also given special mattresses, and administration of corticosteroids is excluded. The results of the 3 day evaluation were that there were no pressure sores found on the client and a reduction in the risk of pressure sores with the achievement of an increase in the Braden score, namely Patient 1 had an increase in the Braden score from a score of 13 (moderate risk of pressure sores) to 15 (mild risk of pressure sores), patient 2 experienced an increase in the Braden score from 13 to 15. Patient 3, a score of 14 to 16 which from a moderate risk to a mild risk of pressure sores. Implementation of intervention delivery repositioning In patients who comply every 2 hours, it is very effective in preventing the occurrence of pressure sores (decubitus) compared to not providing intervention repositioning. So this intervention can be recommended